Enforced Disappearance in Peru: A Step towards a National Policy to Search for Disappeared Persons - Serranò, Agata (The Age of Human Rights Journal, 2022)
This paper aims to explore, firstly, what impact enforced disappearance -committed during the internal armed conflict which occurred between 1980 and 2000 in Peru - had on victims’ family members. Secondly, measures taken by the Peruvian State for the search, exhumation, identification and restitution of the remains of disappeared persons will be examined. Thanks to the analysis of 8 qualitative interviews with family members of disappeared persons and/or leaders of associations dedicated to supporting them, this paper will analyse the needs of family members of disappeared persons, which are still unmet and that constitute a future challenge for the Peruvian state.